(untitled) (Asian Journal of Pharmaceutical and Health Sciences, 2023)
The disease that affects the myelin sheaths that surround nerve cells within spinal cord and brain is multiple sclerosis (MS). The only disease-modifying treatment for primary-progressive MS that has received FDA approval is ocrelizumab (Ocrevus) (DMT). This treatment slightly reduces the likelihood of progression compared to no treatment. Significant health hazards are associated with several of the disease-modifying treatments used to treat MS. Many MS patients employ a variety of complementary or alternative therapies, or perhaps both, to assist manage their symptoms. Although there are few studies to support its utility in controlling MS symptoms, physical and mental health can be enhanced through a variety of practises, some of which are: working out, meditating, doing yoga, getting a massage, eating right, trying acupuncture, and learning to relax. Physical therapy can be used to treat MS and alleviate symptoms such as leg weakness and gait issues. Numerous herbs aid in the treatment of MS which reduces its side effects and symptoms. Multiple studies firmly demonstrate that the anti-inflammatory and anti-oxidant components in medicinal plants naturally have a therapeutic significance for multiple sclerosis. Goal of this paper is to highlight the favourable features of various treatments in managing or treating the symptoms of MS.